"Das Museum der BSD in Soest. Ein Interview mit Burkhard Schnettler" - Huybrechts, Yves

Autonomes Putten mittels datengetriebener und physikbasierter Methoden - Junker, Annika; Fittkau, Niklas; Timmermann, Julia; Trächtler, Ansgar (Proceedings - 32. Workshop Computational Intelligence: Berlin, 1. - 2. Dezember 2022)

Frauen, die sich einmischen. Biblisch-politische Lektüren. Festschrift für Imtraud Fischer

Gottesbilder in den Deuteropaulinen. Metaphernrezeption im Kontext von Bildfeldtraditionen - Taschl-Erber, Andrea (Gottes-Bilder. Zur Metaphorik biblischer Gottesrede)

„Die desinfizierte Gesellschaft. Zwischen Schutz des Sozialen und Entsozialisierung in (post)pandemischen Zeiten“

2.3.5 Übersicht über die verschiedenen Blöcke - Neiske, Iris (#MoodleKannMehr - nicht nur im Distanzunterricht. Visual Ink Publishing)

2.8 Interaktive Übungen mit H5P - Neiske, Iris; Zick, Mirco (#MoodleKannMehr - nicht nur im Distanzunterricht. Visual Ink Publishing)

2.3.4 Blöcke Hinzufügen - Neiske, Iris (#MoodleKannMehr - nicht nur im Distanzunterricht. Visual Ink Publishing)

5.2.3 Etherpad - Neiske, Iris (#MoodleKannMehr - nicht nur im Distanzunterricht. Visual Ink Publishing)

5.2.5 Gegenseitige Beurteilung - Neiske, Iris (#MoodleKannMehr - nicht nur im Distanzunterricht. Visual Ink Publishing)

6.2 Moodle an Hochschulen - Neiske, Iris (#MoodleKannMehr - nicht nur im Distanzunterricht. Visual Ink Publishing)

5.2.4 Foren - Neiske, Iris (#MoodleKannMehr - nicht nur im Distanzunterricht. Visual Ink Publishing)

Tax Avoidance and Vertical Interlocks within Multinational Enterprises - Giese, Henning; Koch, Reinald; Gamm, Markus

Fridolin-Duck Karotti. Mit einem kollaborativem Schreibtool gemeinsam Fantasietiere beschreiben - Rezat, Sara; Scholle, Oliver (Praxis Deutsch)

Kooperation von Elternhaus und Schule zum Thema "digitale Medien". Unterschiede zwischen Elternhäusern und Zusammenhänge mit elterlichen Fähigkeiten zur Nutzung und Gestaltung des Internets sowie Medienerziehung - Bonanati, Sabrina; Kurock, Ricarda; Gruchel, Nicole; Buhl, Heike M. (MedienPädagogik)
Die Kooperation zwischen Elternhaus und Schule kann Eltern in ihren Fähigkeiten zur Internetnutzung und -gestaltung sowie in der Wahl passender Medienerziehungsstrategien ihrer Kinder unterstützen. Voraussetzung dafür ist Wissen darüber, welche Kooperationsangebote Eltern von Schulen zum Thema digitale Medien erhalten. Die vorliegende Studie untersuchte anhand einer Befragung von N = 736 Schülerinnen und Schülern der fünften Klassenstufe und N = 426 ihrer Eltern, welche Informations- und Teilhabeangebote letztere erhielten und wie diese Angebote mit elterlichen Fähigkeiten zur Nutzung und Gestaltung des Internets sowie Medienerziehung zusammenhängen. Eltern erhielten nur zum Teil Informations- und Teilhabeangebote zum Thema ‹digitale Medien›. Eltern mit Migrationshintergrund und Eltern mit niedrigeren bis mittleren Bildungsabschlüssen berichteten aber, häufiger Angebote zu erhalten. Je häufiger Eltern Angebote erhielten, bei denen sie digitale Medien mit ihren Kindern zusammen ausprobieren und erproben konnten, umso geringer waren Fähigkeiten zur Internetnutzung. Dies kann mit der Passung der Angebote von Schulen zu den Bedürfnissen von Eltern zusammenhängen, aber auch ein Anzeichen dafür sein, dass gerade Eltern mit geringeren Fähigkeiten auf Kooperationsangebote von Schulen eingehen. Es wurden keine signifikanten Zusammenhänge zwischen Kooperationsangeboten und Medienerziehung gefunden. Ergebnisse können helfen, vermehrte Angebote für Eltern zu schaffen sowie adressatengerecht zu gestalten.

Family Climate and Social Adaptation of Adolescents in Community Samples: A Systematic Review - Kurock, Ricarda; Gruchel, Nicole; Bonanati, Sabrina; Buhl, Heike M. (Adolescent Research Review)
The family plays an important role in adolescents’ social development. Yet there is little information about the impact of family climate on adolescents’ social adaptation, and the term “family climate” is seldom clearly defined and is usually related to other concepts, such as family systems or family environments. To understand the core of family climate, this study conducted a systematic review to analyze research about family climate associated with adolescents’ social adaptation in community samples. A search of empirical research published over the last 20 years identified 12 relevant studies. The studies revealed that family climate can mainly be described in terms of cohesion, conflict, organization, adaptability, and expressiveness. Family climate was shown to be a good predictor of both problem-solving skills and violence in relationships and exhibited further associations with other aspects of social adaptation. This review revealed a need for more systematic and longitudinal research on family climate in community samples.
Keywords: Family environment; Family system; Adolescents; Social adaptation; Systematic review

Frag mich, dann helfe ich dir – Familienklima und Hilfebitten von Kindern als Gelingensbedingungen für elterliche Unterstützung bei Informationssuchen im Internet - Kurock, Ricarda; Gruchel, Nicole; Bonanati, Sabrina; Buhl, Heike M. (Empirische Pädagogik)

Soziale Disparitäten in der schulbezogenen Internetnutzung von Kindern überwinden: Die Rolle der elterlichen Unterstützung als möglicher Vermittler - Gruchel, Nicole; Kurock, Ricarda; Bonanati, Sabrina; Buhl, Heike M. (Empirische Pädagogik)

Constellations

Einleitung - Haacke-Werron, Stefanie; Karsten, Andrea; Scharlau, Ingrid (Reflexive Schreibwissenschaft. Disziplinäre und praktische Perspektiven)

Sprechen, Schreiben, Denken - Karsten, Andrea (Reflexive Schreibwissenschaft. Disziplinäre und praktische Perspektiven)

The smoots Package in R for Semiparametric Modeling of Trend Stationary Time Series - Feng, Yuanhua; Gries, Thomas; Letmathe, Sebastian; Schulz, Dominik (The R Journal)
Keywords: Statistics; Probability and Uncertainty; Numerical Analysis; Statistics and Probability

Decision-making under Imperfect Information with Bayesian Learning or Heuristic Rules - Burs, Carina; Gries, Thomas
Information is one of the most important ingredients for decision-making. While the neoclassical assumption of perfect information is surely an important conceptual benchmark for discussing efficient allocations, it is obviously far from describing a rational choice under real conditions. In reality, optimal choices should be considered choices under imperfect information. Thus, decision-makers' information problem can be solved by two strategies. Either they collect an optimal set of information to make an optimal allocation choice under this imperfect information set or they can apply heuristic reasoning. In this paper, we suggest a formal model framework for the example of a simple consumer decision for the allocation of differentiated goods to explore information acquisition strategies in such a simple standard choice situation. Using the model variation under perfect information as a benchmark, we answer the following questions. First and most importantly, under imperfect information, can a heuristic rule substitute information acquisition as an optimal choice? Second, what is the role of risk aversion in the information acquisition process? Finally, we explore the differences to the benchmark, both ex ante the first purchase decision and ex post when repeated purchases and consumption allows for experiences with the choices made.
Keywords: information economics; imperfect information; Bayesian learning; risk; heuristics; differentiated products

The smoots Package in R for Semiparametric Modeling of Trend Stationary Time Series - Feng, Yuanhua; Gries, Thomas; Letmathe, Sebastian; Schulz, Dominik (The R Journal)
Keywords: Statistics; Probability and Uncertainty; Numerical Analysis; Statistics and Probability

疫情下遠距教學對差異群體教育公平的影響之探討 - 陳淑敏, 陳淑敏; 林亮雯, 林亮雯 (教育研究月刊)

Put in the time and effort to write rigorous, well-thought-out reviews”: Interview with Greg William Misiaszek, Executive Editor of “Teaching in Higher Education" - Lin-Januszewski, Liang-Wen

Learning Data-Driven PCHD Models for Control Engineering Applications* - Junker, Annika; Timmermann, Julia; Trächtler, Ansgar (IFAC-PapersOnLine)
Keywords: Control and Systems Engineering

Museen sind wie Denkmäler - Hartung, Olaf (BBBank-Magazin Wertsache)
Keywords: Museum Geschichte Exponate

Towards a Process Model for Social Media Marketing - Arslan, Kader; Trier, Matthias (Proceedings of the 33rd Australasian Conference on Information Systems (ACIS 2022))
Keywords: Social media; Social media marketing process; Social media strategy; Social media management; Guidelines

Coquand, Thierry, “Lorenzen and Constructive Mathematics”, in: Gerhard Heinzmann et al. (eds.), Paul Lorenzen – Mathematician and Logician, Springer: Cham 2021 (Logic, Epistemology, and the Unity of Science; 51), 48–61. - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1490.03001)

De Mol, Liesbeth / Bullynck, Maarten, “Making the History of Computing. The History of Computing in the History of Technology and the History of Mathematics”, In: Revue de Synthèse (7) 139 (2018) - Peckhaus, Volker (Mathematical Reviews MR4162129)

Scholz, Heinrich - Peckhaus, Volker (Stanford Encyclopedia of Philosophy)

Einleitung - Peckhaus, Volker (Christian Thiel. Fregeana. Zwölf Studien über Freges Logik)

Beispiel aus der Lehrpraxis: Künstlerische Prozesse am Anfang des Studiums - Pauls, Karina (Schnittstelle Kunstunterricht: Körper - Raum - Skulptur)

Skulptur als Herausforderung für den Kunstunterricht - Pauls, Karina (Schnittstelle Kunstunterricht: Körper - Raum - Skulptur)

Kunstpädagogische Handlungsfelder - Pauls, Karina (Lexikon der Kunstpädagogik)

Arts and Crafts-Bewegung - Pauls, Karina (Lexikon der Kunstpädagogik)

Inszenierung - Pauls, Karina; Nafe, Nadja (Lexikon der Kunstpädagogik)

Installation - Pauls, Karina (Lexikon der Kunstpädagogik)

Schnittstelle Kunstunterricht: Körper - Raum – Skulptur

Materialität - Pauls, Karina (Lexikon der Kunstpädagogik)

Studio Thinking - Pauls, Karina (Lexikon der Kunstpädagogik)

Lernort Schule - Pauls, Karina (Lexikon der Kunstpädagogik)

Relief - Pauls, Karina (Lexikon der Kunstpädagogik)

Werken - Pauls, Karina (Lexikon der Kunstpädagogik)

Rezension zu Kunibert Bering: Kunstunterricht und Bildung. Kulturelles Gedächtnis, Globalität, innovative Perspektiven - Pauls, Karina (Kunst+Unterricht 459/460)

Neuwirth, Stefan, “Lorenzen’s Reshaping of Krull’s Fundamentalsatz for Integral Domains (1938–1953)”, in: Gerhard Heinzmann et al. (eds.), Paul Lorenzen – Mathematician and Logician, Springer: Cham 2021 (Logic, Epistemology, and the Unity of Science; 51), 143–183. - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1484.01013)

Warren, Daniel, "Kant on Mathematics and the Metaphysics of Corporal Nature. The Role of the Infinitesimal”, in: Carl Posy et. al. (eds.), Kant’s Philosophy of Mathematics, Vol. 1: The Critical Philosophy and its Roots, Cambridge University Press: Cambridge 2020, 66–82 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1492.01011)

Antos, Carolin, “Conceptions of Infinity and Set in Lorenzen’s Operationist System”, in: Gerhard Heinzmann et al. (eds.), Paul Lorenzen – Mathematician and Logician, Springer: Cham 2021 (Logic, Epistemology, and the Unity of Science; 51), 23–46. - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1494.03011)

Fermüller, Christian G., "Connecting Sequent Calculi with Lorenzen-Style Dialogue Games", in: Gerhard Heinzmann et al. (eds.), Paul Lorenzen – Mathematician and Logician, Springer: Cham 2021 (Logic, Epistemology, and the Unity of Science; 51) 143–183 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1490.03014)

Tait, W.W., “Kant on Number”, in: Carl Posy et. al. (eds.), Kant’s Philosophy of Mathematics, Vol. 1: The Critical Philosophy and its Roots, Cambridge University Press: Cambridge 2020, 267–291 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1495.01012)

Stuhlmann-Laeisz, Gottlob Freges "Grundgesetze der Arithmetik". Ein Kommentar des Vorworts, des Nachworts und der einleitenden Paragrafen, mentis Verlag: Paderborn 2020 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1481.01035)

Lexikon der Kunstpädagogik

Stable bipolarons in open quantum systems - Moroder, Mattia; Grundner, Martin; Damanet, François; Schollwöck, Ulrich; Mardazad, Sam; Flannigan, Stuart; Köhler, Thomas; Paeckel, Sebastian (Physical Review B 107, 214310 (2023))
Recent advances in numerical methods significantly pushed forward the understanding of electrons coupled to quantized lattice vibrations. At this stage, it becomes increasingly important to also account for the effects of physically inevitable environments. In particular, we study the transport properties of the Hubbard-Holstein Hamiltonian that models a large class of materials characterized by strong electron-phonon coupling, in contact with a dissipative environment. Even in the one-dimensional and isolated case, simulating the quantum dynamics of such a system with high accuracy is very challenging due to the infinite dimensionality of the phononic Hilbert spaces. For this reason, the effects of dissipation on the conductance properties of such systems have not been investigated systematically so far. We combine the non-Markovian hierarchy of pure states method and the Markovian quantum jumps method with the newly introduced projected purified density-matrix renormalization group, creating powerful tensor-network methods for dissipative quantum many-body systems. Investigating their numerical properties, we find a significant speedup up to a factor $\sim 30$ compared to conventional tensor-network techniques. We apply these methods to study dissipative quenches, aiming for an in-depth understanding of the formation, stability, and quasi-particle properties of bipolarons. Surprisingly, our results show that in the metallic phase dissipation localizes the bipolarons, which is reminiscent of an indirect quantum Zeno effect. However, the bipolaronic binding energy remains mainly unaffected, even in the presence of strong dissipation, exhibiting remarkable bipolaron stability. These findings shed light on the problem of designing real materials exhibiting phonon-mediated high-$T_C$ superconductivity.

Statistical analysis of initial state and final state response in heavy-ion collisions - Borghini, Nicolas; Borrell, Marc; Feld, Nina; Roch, Hendrik; Schlichting, Sören; Werthmann, Clemens (Phys. Rev. C 107 (2023) 034905)
We develop a general decomposition of an ensemble of initial density profiles in terms of an average state and a basis of modes that represent the event-by-event fluctuations of the initial state. The basis is determined such that the probability distributions of the amplitudes of different modes are uncorrelated. Based on this decomposition, we quantify the different types and probabilities of event-by-event fluctuations in Glauber and Saturation models and investigate how the various modes affect different characteristics of the initial state. We perform simulations of the dynamical evolution with KoMPoST and MUSIC to investigate the impact of the modes on final-state observables and their correlations.

Plant mitochondrial RNA editing factors can perform targeted C-to-U editing of nuclear transcripts in human cells - Lesch, Elena; Schilling, Maximilian T; Brenner, Sarah; Yang, Yingying; Gruss, Oliver J; Knoop, Volker; Schallenberg-Rüdinger, Mareike (Nucleic Acids Research)
Abstract RNA editing processes are strikingly different in animals and plants. Up to thousands of specific cytidines are converted into uridines in plant chloroplasts and mitochondria whereas up to millions of adenosines are converted into inosines in animal nucleo-cytosolic RNAs. It is unknown whether these two different RNA editing machineries are mutually incompatible. RNA-binding pentatricopeptide repeat (PPR) proteins are the key factors of plant organelle cytidine-to-uridine RNA editing. The complete absence of PPR mediated editing of cytosolic RNAs might be due to a yet unknown barrier that prevents its activity in the cytosol. Here, we transferred two plant mitochondrial PPR-type editing factors into human cell lines to explore whether they could operate in the nucleo-cytosolic environment. PPR56 and PPR65 not only faithfully edited their native, co-transcribed targets but also different sets of off-targets in the human background transcriptome. More than 900 of such off-targets with editing efficiencies up to 91%, largely explained by known PPR-RNA binding properties, were identified for PPR56. Engineering two crucial amino acid positions in its PPR array led to predictable shifts in target recognition. We conclude that plant PPR editing factors can operate in the entirely different genetic environment of the human nucleo-cytosol and can be intentionally re-engineered towards new targets.
Keywords: Genetics

Das Hubble-Teleskop: Mehr als 30 Jahre Beobachtung. - Hohmann, Sascha (Astronomie + Raumfahrt im Unterricht)

Comparison: Stochastics with a Focus on Probability Theory - Stoffels, Gero; Hohmann, Sascha (Comparison of Mathematics and Physics Education II. Examples of Interdisciplinary Teaching at School)

Comparison: Equations in Mathematics and Physics Education - Hohmann, Sascha; Pielsticker, Felicitas (Comparison of Mathematics and Physics Education II. Examples of Interdisciplinary Teaching at School)

Das Stellarium Gornergrat: Ein ferngesteuertes Observatorium für Bildungszwecke. - Gschwind, Stéphane; Hohmann, Sascha; Müller, Andreas; Riesen, Timm-Emanuel (Astronomie + Raumfahrt im Unterricht)

Wie die Wikinger das Nordmeer überqueren konnten - Hohmann, Sascha (Astronomie + Raumfahrt im Unterricht)

Wortkritik als Aufgabenfeld einer diversitätssensiblen Literaturdidaktik. Das Verfahren der Dechiffrierung als ein Weg fachintegrativer Verankerung von Diversitätssensibilität - Kißling, Magdalena (Diversitätsorientierte Deutschdidaktik: Theoretisch-konzeptionelle Fundierung und Perspektiven für empirisches Arbeiten. Band 4 SLLD (B))
Keywords: Diversität; Inklusion; Gender; Deutschdidaktik

‚Nofretete-Mädchen‘ als Aufstörende des Adipositas-Mythos. Interkulturelle Perspektive auf Adoleszenz am Beispiel von Stefanie Höflers Tanz der Tiefseequalle - Kißling, Magdalena (Adoleszenz und Alterität. Synergien aktueller Ansätze der interkulturellen Literaturwissenschaft und -didaktik)

Postkolonialismus. Der Deutschunterricht (5) LXXIV

Politik&Co. Wirtschaft-Politik 9/10, Gymnasium Nordrhein-Westfalen - Dieckmann, Eva; Kißling, Magdalena; Labusch, Alexandra; Lindner, Nora; Mertens, Julia; Rohde, Marius

Eine kulinarische Geschlechterordnung? Die Polarisierung von Geschlecht im Kontext medialer Inszenierung und alltagsweltlicher Darstellungen des Kulinarischen - Eremin, Oxana (GENDER. Zeitschrift für Geschlecht, Kultur und Gesellschaft)

#FeministKitchen [Notes] - Eremin, Oxana (FKW//Zeitschrift für Geschlechterforschung und visuelle Kultur)

(K)Eine Frage des Wissens: Zum Verhältnis von Gender Studies & Wissenstransfer - Eremin, Oxana; Krämer, Anike; Mattei, Annalisa (Wissenstransfer als Aufgabe, Herausforderung und Chance kulturwissenschaftlicher Forschung.)

Foodwork: Schlaglichter auf das Themenfeld von Essen, Kochen und Geschlecht - Eremin, Oxana (Soziale Passagen. Journal für Empirie und Theorie Sozialer Arbeit)

Effects of strong fringing magnetic fields on turbulent thermal convection - Bhattacharya, Shashwat; Boeck, Thomas; Krasnov, Dmitry; Schumacher, Jörg (arXiv:2211.00559)
We study the influence of fringing magnetic fields on turbulent thermal convection in a horizontally extended rectangular domain. The magnetic field is created in the gap between two semi-infinite planar magnetic poles, with the convection layer located near the edge of the gap. We employ direct numerical simulations in this setup for fixed Rayleigh and small Prandtl numbers, but vary the fringe-width by controlling the gap between the magnetic poles and the convection cell. The magnetic field generated by the magnets is strong enough to cease the flow in high magnetic flux region of the convection cell. We observe that as the local vertical magnetic field strength increases, the large scale structures become thinner and align themselves perpendicular to the longitudinal sidewalls. We determine the local Nusselt and Reynolds numbers as functions of the local Hartmann number (based on the vertical component of the magnetic field) and estimate the global heat and momentum transport. We show that the global heat transport decreases with increasing fringe-width for strong magnetic fields but increases with increasing fringe-width for weak magnetic fields. In the regions of large vertical magnetic fields, the convective motion becomes confined to the vicinity of the sidewalls. The amplitudes of these wall modes show a non-monotonic dependence on the fringe-width.

Agnostic Explanation of Model Change based on Feature Importance - Muschalik, Maximilian; Fumagalli, Fabian; Hammer, Barbara; Hüllermeier, Eyke (KI - Künstliche Intelligenz)
Abstract Explainable Artificial Intelligence (XAI) has mainly focused on static learning tasks so far. In this paper, we consider XAI in the context of online learning in dynamic environments, such as learning from real-time data streams, where models are learned incrementally and continuously adapted over the course of time. More specifically, we motivate the problem of explaining model change , i.e. explaining the difference between models before and after adaptation, instead of the models themselves. In this regard, we provide the first efficient model-agnostic approach to dynamically detecting, quantifying, and explaining significant model changes. Our approach is based on an adaptation of the well-known Permutation Feature Importance (PFI) measure. It includes two hyperparameters that control the sensitivity and directly influence explanation frequency, so that a human user can adjust the method to individual requirements and application needs. We assess and validate our method’s efficacy on illustrative synthetic data streams with three popular model classes.
Keywords: Artificial Intelligence

VALIDATION AND COMPARISON OF FEM-SIMULATION RESULTS OF THE FUSED DEPOSITION MODELING PROCESS UNDER CONSIDERATION OF DIFFERENT MESH RESOLUTIONS - Moritzer, Elmar; Hecker, Felix (Proceedings of the 33rd Annual Freeform Fabrication Symposium)

New York als Material - Künstlerische Forschung im Spannungsfeld von Kunstgeschichte, Kunstpraxis und Vermittlung - Autsch, Sabiene (Kunstpädagogik und ... Bezugsfelder und Perspektiven kunstpädagogischer Theorie und Praxis)

Die ASK und ihre Ausstellungen. Ein Visual Essay - Autsch, Sabiene; Pickartz, Tim (Bis hierhin und weiter. Hundert Jahre Arbeitsgemeinschaft Siegerländer Künstlerinnen und Künstler [= Publikation anlässlich der gleichnamigen Ausstellung, Städtische Galerie Haus See, Siegen, 29. Mai - 03. Juli 2022])

Mikroformen - Autsch, Sabiene (Lexikon der Kunstpädagogik)

Elegische Liebestragödie. Johann Elias Schlegels "Die Trojanerinnen" (1737/47) - Puscher, Sahra (ZwischenSpielZeit. Das Theater der Frühaufklärung (1680-1730))

Erkenntnisse zur Verbesserung von Mentoringprozessen in der Lehrer:innenausbildung - Goller, Michael; Caruso, Carina; Harteis, Christian (SEMINAR – Lehrerbildung und Schule)

Möglichkeiten und Grenzen der Messung, Kontrolle und Sicherung der Qualität logistischer Prozesse - Hrnjadovic, Damir (Aktuelle Fragestellungen zu Produktion, Logistik und Controlling)

Implikationen einer wertorientierten Unternehmensführung für Standortplanungsentscheidungen - Fiedler, Moritz (Aktuelle Fragestellungen zu Produktion, Logistik und Controlling)

Betriebliche Standortplanung international agierender Unternehmen - Osthoff, Lennart (Aktuelle Fragestellungen zu Produktion, Logistik und Controlling)

Kategorisierungsmöglichkeiten für die Erzeugung von Dienstleistungen - Opitz, Oliver (Aktuelle Fragestellungen zu Produktion, Logistik und Controlling)

Entscheidungsunterstützung durch das Controlling mittels Reporting Design - Faupel, Christian (Aktuelle Fragestellungen zu Produktion, Logistik und Controlling)

Aktuelle Fragestellungen zu Produktion, Controlling und Logistik

Strom statt Gas: Nachhaltige Herstellung von Karosseriebauteilen - Pfeifer, Florian; Jungeilges, André; Behm, Jonathan (Transforming Economies)

Gekoppelte Simulation des resistiven Schnellerwärmens für Fertigungsprozesse mit integrierter Wärmebehandlung am Beispiel der Titanlegierung Ti-6Al-4V - Merten, Mathias; Klöppel, Thomas; Haufe, André; Kaiser, Maximilian Alexander; Wesendahl, Jan-Niklas; Konrad, Stefan (Workshop Warmblechumformung)
Der Beitrag liefert einen Überblick über die Möglichkeiten der gekoppelten multiphysikalischen numerischen Simulation mit dem Finite Elemente-Löser LS-DYNA. Am Beispiel der resistiven Schnellerwärmung einer Titanlegierung im Forschungsprojekt TISTRAQ erfolgt die Beschreibung der Vorgehensweise, der Eingangs- und Ergebnisgrößen sowie der weiteren Anwendung der Simulation im Forschungsprojekt. Im Fokus steht dabei die Ermittlung der lokalen Temperaturverläufe, deren Kenntnis eine Grundvoraussetzung für die Berechnung prozessabhängiger Materialkennwerte darstellt.

Heat transfer coefficient investigation for hot die quenching process of Ti-6Al-4V alloy - Kaiser, Maximilian Alexander; Rockicki, Pawel; Höschen, Fabian; Wesendahl, Jan-Niklas; Konrad, Stefan; Meyer, Thomas; Marten, Thorsten; Tröster, Thomas
In the aerospace industry processing of high strength titanium alloys is both resource and time consuming. That why a lot of efforts is put on development of new and highly advanced manufacturing processes as hot die quenching. The process is based on combination of elevated temperature plastic forming with modification of the microstructure due to heat treatment, and thus increase in the properties of finally shaped geometry. One of the most crucial factors in the hot die quenching process is heat transfer coefficient. It is a main driver for adjustment of basic process parameters, as selection of tool material or the strain rate, but also plays an important role while elaborating temperature field in the numerical model. Thus, the main scope of the research within the current study is to examinate the heat transfer coefficient (HTC) for titanium and tooling material, which correspond to a real forming process. New and unique test stand have been designed and presented together with preliminary experimental results, which are a basis for further numerical simulation model of the hot die quenching process.
Keywords: Ti-6Al-4V; heat transfer coefficient

Isothermal hot forming of Titanium sheet metal - From parameter identification to custom parts - Kaiser, Maximilian Alexander; Wesendahl, Jan-Niklas; Meyer, Thomas

Process Mining of Knowledge-Intensive Processes: An Action Design Research Study in Manufacturing - Löhr, Bernd; Brennig, Katharina; Bartelheimer, Christian; Beverungen, Daniel; Müller, Oliver (International Conference on Business Process Management)
Existing process mining methods are primarily designed for processes that have reached a high degree of digitalization and standardization. In contrast, the literature has only begun to discuss how process mining can be applied to knowledge-intensive processes—such as product innovation processes—that involve creative activities, require organizational flexibility, depend on single actors’ decision autonomy, and target process-external goals such as customer satisfaction. Due to these differences, existing Process Mining methods cannot be applied out-of-the-box to analyze knowledge-intensive processes. In this paper, we employ Action Design Research (ADR) to design and evaluate a process mining approach for knowledge-intensive processes. More specifically, we draw on the two processes of product innovation and engineer-to-order in manufacturing contexts. We collected data from 27 interviews and conducted 49 workshops to evaluate our IT artifact at different stages in the ADR process. From a theoretical perspective, we contribute five design principles and a conceptual artifact that prescribe how process mining ought to be designed for knowledge-intensive processes in manufacturing. From a managerial perspective, we demonstrate how enacting these principles enables their application in practice.

(How) do advanced data and analyses enable HR analytics success? A neo-configurational analysis - Strohmeier, Stefan; Collet, Julian; Kabst, Rüdiger (Baltic Journal of Management)
Purpose Enabled by increased (“big”) data stocks and advanced (“machine learning”) analyses, the concept of human resource analytics (HRA) is expected to systematically improve decisions in human resource management (HRM). Since so far empirical evidence on this is, however, lacking, the authors' study examines which combinations of data and analyses are employed and which combinations deliver on the promise of improved decision quality. Design/methodology/approach Theoretically, the paper employs a neo-configurational approach for founding and conceptualizing HRA. Methodically, based on a sample of German organizations, two varieties (crisp set and multi-value) of qualitative comparative analysis (QCA) are employed to identify combinations of data and analyses sufficient and necessary for HRA success. Findings The authors' study identifies existing configurations of data and analyses in HRM and uncovers which of these configurations cause improved decision quality. By evidencing that and which combinations of data and analyses conjuncturally cause decision quality, the authors' study provides a first confirmation of HRA success. Research limitations/implications Major limitations refer to the cross-sectional and national sample and the usage of subjective measures. Major implications are the suitability of neo-configurational approaches for future research on HRA, while deeper conceptualizing and researching both the characteristics and outcomes of HRA constitutes a core future task. Originality/value The authors' paper employs an innovative theoretical-methodical approach to explain and analyze conditions that conjuncturally cause decision quality therewith offering much needed empirical evidence on HRA success.
Keywords: Management of Technology and Innovation; Marketing; Organizational Behavior and Human Resource Management; Strategy and Management; Business and International Management

Like It or not: When corporate social responsibility does not attract potential applicants - Jakob, Eva Alexandra; Steinmetz, Holger; Wehner, Marius; Engelhardt, Christina; Kabst, Rüdiger (Journal of Business Ethics)

The case of Mesut Özil: A symbol of (non-) integration? An analysis of German print media discourses on integration - Schmidt, Eva (Discourse & Communication)

Die Erde und die Welt. Wie wir Hannah Arendt in Anthropozän lesen können - Robaszkiewicz, Maria Anna (Anfangen! Politik im Anthropozän. Beiträge der 24. Hannah Arendt Tage 2021)

Georg Brunn/Claus Beisbard [Hg.], Mit Philosophie die Welt verändern, Basel: Schwabe Verlag 2020 - Robaszkiewicz, Maria Anna (Zeitschrift für Didaktik der Philosophie und Ethik)

HybridFC: A Hybrid Fact-Checking Approach for Knowledge Graphs - Qudus, Umair; Röder, Michael; Saleem, Muhammad; Ngonga Ngomo, Axel-Cyrille (The Semantic Web -- ISWC 2022)
We consider fact-checking approaches that aim to predict the veracity of assertions in knowledge graphs. Five main categories of fact-checking approaches for knowledge graphs have been proposed in the recent literature, of which each is subject to partially overlapping limitations. In particular, current text-based approaches are limited by manual feature engineering. Path-based and rule-based approaches are limited by their exclusive use of knowledge graphs as background knowledge, and embedding-based approaches suffer from low accuracy scores on current fact-checking tasks. We propose a hybrid approach—dubbed HybridFC—that exploits the diversity of existing categories of fact-checking approaches within an ensemble learning setting to achieve a significantly better prediction performance. In particular, our approach outperforms the state of the art by 0.14 to 0.27 in terms of Area Under the Receiver Operating Characteristic curve on the FactBench dataset. Our code is open-source and can be found at https://github.com/dice-group/HybridFC.
Keywords: fact checking · ensemble learning · knowledge graph veracit

The broken chain: Evidence against emotionally driven upstream indirect reciprocity - Schnedler, Wendelin (Games and Economic Behavior)
Psychologists claim that being treated kindly puts individuals in a positive emotional state: they then treat an unrelated third party more kindly. Numerous experiments document that subjects indeed ‘pay forward’ specific behavior. For example, they are less generous after having experienced stinginess. This, however, is not necessarily driven by emotions. Subjects may also imitate what they regard as socially adequate behavior. Here, I present an experiment in which imitation is not possible at the next opportunity to act with a stranger: after being given either a fun or an annoying job, subjects have to decide whether to be generous or not. I find that although subjects who are given the annoying job report more negative emotions than those with the fun job, they do not treat an unrelated third person more unkindly in terms of passing on less money.
Keywords: Economics and Econometrics; Finance

Shortcut Learning in Financial Text Mining: Exposing the Overly Optimistic Performance Estimates of Text Classification Models under Distribution Shift - Caron, Matthew (2022 IEEE International Conference on Big Data (Big Data))
In recent years, many cases of deep neural networks failing dramatically when faced with adversarial or real-world examples have been reported. Such failures, which are quite hard to detect, are often related to a generalization problem known as shortcut learning. Yet, with state-of-the-art transformer models now being ubiquitous in financial text mining, one cannot help but wonder how reliable the results conveyed in the ever-growing literature genuinely are. Against this background, we expose, in this work, how vulnerable contemporary financial text mining approaches are to shortcut learning. Focussing on the common learning task of financial sentiment classification, we assess, using two entity-based sampling strategies and our publicly-available dataset, the discrepancies between i.i.d. and o.o.d. performance estimates of four transformer models. Our results reveal that o.o.d. performance estimates are consistently weaker than those of their i.i.d. counterparts, with the error rate increasing by as much as 29.7%, thus, demonstrating how this issue can, when overlooked, lead to misleading evaluations. Moreover, we show how additional preprocessing steps, such as entity removal and vocabulary filtering, can help reduce the effects of shortcut learning by filtering out entity-related linguistic cues.

Towards Automated Moderation: Enabling Toxic Language Detection with Transfer Learning and Attention-Based Models - Caron, Matthew; Bäumer, Frederik S.; Müller, Oliver (55th Hawaii International Conference on System Sciences (HICSS))
Our world is more connected than ever before. Sadly, however, this highly connected world has made it easier to bully, insult, and propagate hate speech on the cyberspace. Even though researchers and companies alike have started investigating this real-world problem, the question remains as to why users are increasingly being exposed to hate and discrimination online. In fact, the noticeable and persistent increase in harmful language on social media platforms indicates that the situation is, actually, only getting worse. Hence, in this work, we show that contemporary ML methods can help tackle this challenge in an accurate and cost-effective manner. Our experiments demonstrate that a universal approach combining transfer learning methods and state-of-the-art Transformer architectures can trigger the efficient development of toxic language detection models. Consequently, with this universal approach, we provide platform providers with a simplistic approach capable of enabling the automated moderation of user-generated content, and as a result, hope to contribute to making the web a safer place.

Commentaries on Relationship Marketing: The Present and Future of Customer Relationships in Services - Steinhoff, Lena; Palmatier, R. W.; Martin, K. D.; Fox, G.; Henderson, C. M.; Saint Clair, J. K.; Yan, S.; Lee, J.-Y.; Perko, T.; Harmeling, C. M. (Journal of Service Management Research)

Theorizing Marketplace Solidarity Systems: From Consumer–Firm Dyads to Structures of Mutual Support - Alberternst, B.; Steinhoff, Lena; Eggert, A.; Giesler, M. (2022 AMA Summer Marketing Educators’ Conference Proceedings, Chicago)

How Do I Tell Them? Analyzing Companies' Provision of Rejection Reasons in Product Testing Programs - Garnefeld, I.; Steinhoff, Lena; Küpper, K. (2022 AMA Winter Marketing Educators’ Conference Proceedings, Las Vegas)